Agroforestry Systems in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
edited by P.K.R. Nair, 1989 price DF1300. US$ 175. UKL.97, ISBN 90 247 3790 7 (hardback), published in association with ICRAF, available from: Kluwer Academic Publishers Spuiboulevard 50- PO Box 17 3300 AA Dordrecht THE NETHERLANDS